2014
DOI: 10.1007/978-94-007-5730-1_2
|View full text |Cite
|
Sign up to set email alerts
|

Cartilage of Marine Vertebrates

Abstract: Cartilage is primarily composed of a specialised extracellular matrix synthesised by chondrocytes and contains of the numerous molecules (collagens, polysaccharides, low molecular peptides). This biological material represents unique avascular tissue. This chapter considers the current state-of-the-art biomaterial characterisation of both non-mineralized and mineralized (calcifi ed) cartilages, with respect to the future tissues in biomimetical and biomedical applications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 90 publications
(106 reference statements)
0
9
0
Order By: Relevance
“…It is recognized that so-called spongioblasts—derived from the epithelium of sponges—are responsible for the formation of spongin. Minchin claims that the fibers of skeletal spongin are formed extracellularly; however, the cuticular spongin fibrils are of intracellular origin [ 19 ]. In contrast to such structural proteins as collagen, fibroin (silk), elastin, resilin, and keratin, the chemistry and molecular biology—including the sequences—of spongins so far remain unknown.…”
Section: Spongins As Enigmatic Structural Proteins In Spongesmentioning
confidence: 99%
See 1 more Smart Citation
“…It is recognized that so-called spongioblasts—derived from the epithelium of sponges—are responsible for the formation of spongin. Minchin claims that the fibers of skeletal spongin are formed extracellularly; however, the cuticular spongin fibrils are of intracellular origin [ 19 ]. In contrast to such structural proteins as collagen, fibroin (silk), elastin, resilin, and keratin, the chemistry and molecular biology—including the sequences—of spongins so far remain unknown.…”
Section: Spongins As Enigmatic Structural Proteins In Spongesmentioning
confidence: 99%
“…Marine vertebrate collagens have attracted scientific attention, mostly as products of fisheries [ 19 ]. In particular, fish-sourced collagens from skins and scales [ 20 , 21 , 22 ] have been studied and used as alternative collagen sources to avoid the potential risks associated with mammalian collagen due to bovine spongiform encephalopathy and the swine influenza crisis [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, a few recent studies have also demonstrated that low molecular weight polypeptides from the T-cell determinant of human CII possess the ability to suppress T-cell activation in rheumatoid arthritis (RA), both in vitro and in the development of collagen induced arthritis (CIA) (Myers et al 2004). Recently, few studies have been focused on the preparation and biomedical application of type-II collagen peptides from cartilagous fish species (Ehrlich 2015;Xie et al 2014). To the best of our knowledge, the physicochemical and functional properties of these low molecular weight type-II collagenous polypeptides have not yet been reported.…”
Section: Introductionmentioning
confidence: 99%
“…For the first time in scientific literature, the author gives the most coherent analysis of the nature, origin and evolution of biomaterials and biopolymers isolated from marine sources. Moreover, the variety of marine vertebrate organisms (fish, reptilian, birds and mammals) and within their unique hierarchically organized structural formations has been highlighted [ 61 ]. This can be a reference for performing future studies and research about the possibility of using chitin and collagen marine in the field of the biomedicine.…”
Section: Discussionmentioning
confidence: 99%